PENGGUNAAN APLIKASI ALAT MUSIK PIANIKA DALAM PEMBELAJARAN LAGU CUBLAK-CUBLAK SUWENG PADA MATA PELAJARAN SENI BUDAYA KELAS 5 SD - Wijayanti, Santika Dwi; Aristianti, Siska Dwi; Wijayanto, Wasis (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the effectiveness of using a pianika musical instrument application in learning the traditional song Cublak-Cublak Suweng in the Cultural Arts subject for Grade 5 students at SD Negeri Mejobo. The research method used is descriptive qualitative with a case study approach. Data collection techniques include observation, interviews, and documentation. The results of the study show that the use of the pianika application in learning can increase students’ interest, motivation, and skills in playing traditional songs. The consistent application of the drill method has a positive impact on the mastery of pianika playing techniques, the ability to read musical notation, fine motor coordination, and students’ understanding of melody and rhythm. In addition, this learning media creates a more active, interactive, and enjoyable learning environment. Thus, the use of the pianika application has proven to be an effective learning strategy to introduce traditional songs while fostering students’ appreciation of local culture.